2013
DOI: 10.1158/1078-0432.ccr-13-0621
|View full text |Cite
|
Sign up to set email alerts
|

HAb18G/CD147 Promotes pSTAT3-Mediated Pancreatic Cancer Development via CD44s

Abstract: Purpose STAT3 plays a critical role in initiation and progression of pancreatic cancer. However, therapeutically targeting STAT3 is failure in clinic. We previously identified HAb18G/CD147 as an effective target for cancer treatment. In this study, we aimed to investigate potential role of HAb18G/CD147 in STAT3-involved pancreatic tumorigenesis in vitro and in vivo. Experimental Design The expression of HAb18G/CD147, pSTAT3 and CD44s were determined in tissue microarrays. The tumorigenic function and molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 49 publications
2
58
0
1
Order By: Relevance
“…As shown in Figure 5E, FLLL32, a specific STAT3 inhibitor 26, 28 that moderately inhibits tumorsphere formation alone, significantly enhanced the H4C4-induced tumorsphere inhibition, from 40.8 ± 0.009% inhibition by H4C4 alone to 60.3 ± 0.021% inhibition when combined with H4C4 ( P < 0.001). Similarly, the specific survivin inhibitor YM155 also enhanced H4C4-mediated tumorsphere inhibition ( P < 0.001).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…As shown in Figure 5E, FLLL32, a specific STAT3 inhibitor 26, 28 that moderately inhibits tumorsphere formation alone, significantly enhanced the H4C4-induced tumorsphere inhibition, from 40.8 ± 0.009% inhibition by H4C4 alone to 60.3 ± 0.021% inhibition when combined with H4C4 ( P < 0.001). Similarly, the specific survivin inhibitor YM155 also enhanced H4C4-mediated tumorsphere inhibition ( P < 0.001).…”
Section: Resultsmentioning
confidence: 82%
“…We observed that CD44s was highly expressed in PANC-1, MIA PaCa-2, AsPC-1 and HS-766T cell lines, as well as in human pancreatic cancer primary tumor early passage xenograft, J-2 (Figure 1D–E). Based on this result and our previous observation 11, 26 that PANC-1 and MIA PaCa-2 are highly tumorigenic in vivo and reproducibly form tumorspheres in vitro , these two cell lines as well as early passage xenograft, J-2, were selected for the current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is proposed that by its interaction with STAT3, CypD can regulate the G1 to S phase transition. Furthermore, recent work has demonstrated that CypA stimulates phosphorylation of STAT3 and transcription of cyclin D1/surviving [107].…”
Section: Cytokinesis Failure and Cancermentioning
confidence: 99%